2016
DOI: 10.1007/s11121-016-0653-4
|View full text |Cite
|
Sign up to set email alerts
|

Strategies to Overcome Barriers to Implementation of Alcohol Screening and Brief Intervention in General Practice: a Delphi Study Among Healthcare Professionals and Addiction Prevention Experts

Abstract: Despite the evidence base, alcohol screening and brief intervention (ASBI) have rarely been integrated into routine clinical practice. The aim of this study is to identify strategies that could tackle barriers to ASBI implementation in general practice by involving primary healthcare professionals and addiction prevention experts. A three-round online Delphi study was carried out in the Netherlands. The first-round questionnaire consisted of open-ended questions to generate ideas about strategies to overcome b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 32 publications
2
42
0
Order By: Relevance
“…Another limitation is the suboptimal response rate, ranging from 29% to 42%. Although these percentages are not optimal, they are comparable to other Delphi studies [26, 28, 38]. Finally, consulting consumers in addition to experts may expose important differences between these groups.…”
Section: Discussionsupporting
confidence: 75%
“…Another limitation is the suboptimal response rate, ranging from 29% to 42%. Although these percentages are not optimal, they are comparable to other Delphi studies [26, 28, 38]. Finally, consulting consumers in addition to experts may expose important differences between these groups.…”
Section: Discussionsupporting
confidence: 75%
“…GPs and nurses often cited improving professional teamwork (e.g. having a practice nurse delivering SBI, having receptionists giving patients screening tools) as a facilitator [ 39 , 41 , 54 , 70 , 71 , 73 , 76 , 80 , 91 , 93 , 97 , 99 ].…”
Section: Resultsmentioning
confidence: 99%
“…Three studies on nurses found that most believed in the efficacy of brief interventions [ 70 , 73 , 84 ]. More information about the effectiveness of brief interventions [ 23 , 36 , 39 , 47 , 78 , 84 , 87 , 92 ] and feedback on successful cases [ 71 , 109 ] were identified as implementation facilitators.…”
Section: Resultsmentioning
confidence: 99%
“…Still, people with substance use problems form a complex, heterogeneous group and health providers can be under‐equipped to address AOD issues. Limited AOD knowledge and confidence are among the professional barriers that results in practitioners' low engagement with AOD issues , along with limited opportunities to gain practical AOD experience during role training .…”
Section: Introductionmentioning
confidence: 99%